(3GdEYQGH Yf bhGYO GdEYQGHs - (3GdCfUGQj GdeUQj, CHh eMeO, GHf gTGe, LeGd GdOjf, YHOGddg Hf jhSa Hf CMeO Hf YHOGddg, J (B761 (3g`s
(3ChdgG (B:s
(3bGdLeGd GdOjf GHf gTGe gPg ahGFO LdjdI aj bhGYO GdEYQGHhSejJgG HGdEYQGH Yf bhGYO GdEYQGHs
(3BNQgG (B:s
(3hcKjQ ef GdeJbOejf jSehf GdRGFOI UdI hHYVge jSehf eDcOG haj gPG GdbOQ caGjI def JCedgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 147s
(3eYLe GdeDdajf(B: 2 / 305s
(3cTa GdXfhf(B: 1 / 124s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs